Cost-effectiveness analysis of additional local prostate radio therapy in metastatic prostate cancer from a medicare perspective - Kristina K. M. Kramer; Nina-Sophie Schmidt-Hegemann; Thilo Westhofen; Marco Foglar; Jens Ricke; C. Benedikt Westphalen; Marcus Unterrainer; Wolfgang G. Kunz; Dirk Mehrens (Radiation Oncology)
Abstract Background Metastatic prostate cancer remains a therapeutic challenge. Based on data of the STAMPEDE trial, patients with a low metastatic burden showed prolonged failure-free and overall survival when treated with prostate radio therapy (RT) in addition to standard of care (SOC). The objective of this study was to determine the cost-effectiveness of additional prostate RT compared to SOC alone for following subgroups: non-regional lymph node (NRLN) metastases, up to three bone metastases and four or more bone metastases. Methods A partitioned survival model was implemented with clinical data from STAMPEDE trial. Analyses were performed from a United States healthcare system perspective. Costs for treatment and adverse events were derived from Medicare coverage. Utilities for health states were derived from public databases and literature. Outcome measurements included incremental costs, effectiveness, and cost-effectiveness ratio. The willingness-to-pay threshold was set to USD 100,000 per quality-adjusted life year (QALY). Results Additional RT led to 0.92 incremental QALYs with increased costs of USD 26,098 with an incremental cost-effectiveness ratio (ICER) of USD 28,452/QALY for patients with only NRLN metastases and 3.83 incremental QALYs with increased costs of USD 153,490 with an ICER of USD 40,032/QALY for patients with up to three bone metastases. Sensitivity analysis showed robustness of the model regarding various parameters. In probabilistic sensitivity analysis using Monte Carlo simulation with 10,000 iterations, additional RT was found as the cost-effective strategy in over 96% for both subgroups iterations at a willingness-to-pay threshold of USD 100,000/QALYs. Conclusions Additional RT is cost-effective in patients with only NRLN metastases and up to three metastases compared to SOC.